Odpowiedzi

2010-01-12T22:00:30+01:00
(8 + (-3)^2) /2,75 - 0,5* 1,5 = (8 +9 )/2,75 - 0,75 = 17 /2 = 8,5
(3 + (-5)^2) / 2,65 - 1,3 * 0,5 = (3+ 25) / 2,65 - 0,65 = 28 /2 = 14
Najlepsza Odpowiedź!
2010-01-12T22:00:39+01:00
8+(-3)do kwadratu:(2,75-0,5 *1,5) = 8+ 9: ( 2.75 - 0.75) = 8 + 9 : 2 = 8 + 4.5 = 12,5




3+(-5)do kwadratu:(2,65-1,3*0,5) = 3 + 25 : ( 2.65 - 0.65) = 3 + 25 : 2 = 3 + 12.5 = 15,5
1 1 1
2010-01-12T22:07:05+01:00
8+(-3)do kwadratu:(2,75-0,5 *1,5) = 8 - 9 : (2,75 - 0,5 * 1,5) = 8 - 9 : (2,75 - 0,75) = 8 - 9 : 2 = -1 - 4,5 = -5,5

3+(-5)do kwadratu:(2,65-1,3*0,5) = 3 - 25 : (2,65 - 1,3 * 0,5) = 3 - 25 : (2,65 - 65) = 3 - 25 : 2 = -22 - 12,5 = -33,5